PEMBERIAN WASIAT WAJIBAH KEPADA KELUARGA NON-MUSLIM PERSPEKTIF IMAM SYAFI’I - Basyir, Ahmad; Fitrianoor, Wahyu; Hayati, Anisah Norlaila (Program Studi Hukum Keluarga Islam STAI Al-Falah Banjarbaru, 2024)
AbstractThe granting of a mandatory will to a non-Muslim family is something new in the study of inheritance law, mandatory wills are included in the ijtihadiyah issue because there has not been a Nash argument that explains this implicitly. So the argument put forward is the argument of inheritance and wills, considering that the law applies according to the place of residence and in Indonesia the majority of the population is Shafi'iyah, so this issue must be reviewed from the perspective of Imam Shafi'i. This study focuses on the granting of mandatory wills to non-Muslim families from the perspective of Imam Shafi'i.This study is classified as a type of normative research with a normative legal approach. The primary legal material in this study is the book Al-Umm volume 5 and secondary legal materials in the form of the Compilation of Islamic Law and other books and scientific papers related to wills. The legal materials collected are then analyzed so that conclusions can be drawn.The results of this study are that according to Imam Shafi'i, religious differences are an obstacle to inheritance by adhering to the hadith prohibiting mutual inheritance for those of different religions. Imam Syafi'i also believes that the meaning of the word